2018
DOI: 10.1016/j.fertnstert.2018.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal microbiota, women's health, and reproductive outcomes

Abstract: The human microbiome project has shown a remarkable diversity of microbial ecology within the human body. The vaginal microbiota is unique in that in many women it is most often dominated by Lactobacillus species. However, in some women it lacks Lactobacillus spp. and is comprised of a wide array of strict and facultative anaerobes, a state that broadly correlates with increased risk for infection, disease, and poor reproductive and obstetric outcomes. Interestingly, the level of protection against infection c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
147
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 124 publications
5
147
0
11
Order By: Relevance
“…displayed a similar predictive ability for the disease as the classifier based on POF-associated genetic variants (which had an AUC of 0.841, sensitivity of 71.4%, specificity of 100%, and cut-off rate of 43.2%), implying that the microbial signature that we identified could represent a powerful tool for the prediction of POF. Our results of the changes in relative abundance of particular genera in the context of POF confirm that species of the dominant vaginal genus, Their dominance in the vaginal niche indicate that Lactobacillus are the dominant facultative anaerobes of the genital tract, supported by their presence in most women[31,32].In women with higher levels of basal FSH and lower levels of basal E2, there were fewer Lactobacillus in the vagina than the control group. Eade et al evaluated the presence of Lactobacillus spp in confluent monolayers of endocervical, ectocervical, and vaginal epithelial cells and they found that the majority of Lactobacillus caused a significant decrease in the expression of AMPs, although…”
supporting
confidence: 75%
“…displayed a similar predictive ability for the disease as the classifier based on POF-associated genetic variants (which had an AUC of 0.841, sensitivity of 71.4%, specificity of 100%, and cut-off rate of 43.2%), implying that the microbial signature that we identified could represent a powerful tool for the prediction of POF. Our results of the changes in relative abundance of particular genera in the context of POF confirm that species of the dominant vaginal genus, Their dominance in the vaginal niche indicate that Lactobacillus are the dominant facultative anaerobes of the genital tract, supported by their presence in most women[31,32].In women with higher levels of basal FSH and lower levels of basal E2, there were fewer Lactobacillus in the vagina than the control group. Eade et al evaluated the presence of Lactobacillus spp in confluent monolayers of endocervical, ectocervical, and vaginal epithelial cells and they found that the majority of Lactobacillus caused a significant decrease in the expression of AMPs, although…”
supporting
confidence: 75%
“…Up to now, the research on the distribution of female reproductive flora is mainly focuses on vaginal microbiota or limited to small-scale exploratory on the single site [22][23][24]. Although the previous study has found the intrauterine bacterial colonization in EMS patients by 16S rRNA gene sequencing analysis, the study did not establish a control group [15].…”
Section: Discussionmentioning
confidence: 98%
“…These include uterine factors 70 (eg, intrauterine adhesions, 73,74 uterine myomas, 75 and endometrial polyps 76 ), endometriosis, 77 ovarian function, 78 oviduct obstruction, 79,80 maternal diseases such as diabetes mellitus, 81 immune disorders, 82,83 and the uterine microbiota. 84,85 Because these factors cannot be detected by the AI classifier from an image of the blastocyst, the accuracy, sensitivity, and specificity for live birth cannot reach 1. These clinical characteristics of the blastocyst prevent the accuracy of predicting live birth by any means from reaching close to 1.…”
Section: Discussionmentioning
confidence: 99%